Effectiveness of a Health Literacy and Health Behavior 3E 2S Enhancement Program among Elderly in Pathum Thani Province - Yothasupap, Aussadawut; Ungcharoensuk, Jaroenchai; Ounhalekjit, Pakpoom (Health Science Journal of Thailand, 2025)
The purpose of this study was to evaluate the effectiveness of a program designed to promote health literacy and health behavior according to the 3E 2S principles for the elderly in Pathum Thani Province. This was a quasi-experimental study. The sample consisted of elderly individuals aged 60 years and over in Pathum Thani Province. A total of 80 participants were randomly selected using multi-stage sampling, divided into 40 individuals in the experimental group and 40 in the control group. The program consisted of a learning activity plan lasting 8 weeks, with a follow-up period of 12 weeks. The researcher specifically selected the experimental group. The research instrument was a questionnaire. Statistical analyses used included frequency, percentage, mean, standard deviation, independent t-test, and repeated measures analysis of variance. The results of the study found that comparing health literacy and health behavior between the experimental and comparison groups at each time period, it was found that before the experiment, health literacy and health behavior were not different. After participating in the program for 8 weeks and following up for 12 weeks, the experimental group and comparison group had health literacy and health behavior according to the principles of 3A.2S. They were significantly different at the 0.05 level. And comparing health literacy and health behavior according to the principles of 3A.2S in each experimental group. It was found that health literacy and health behavior according to the principles of the 12-week follow-up period were higher than after using the 8-week model and before using the model, respectively at the statistical significance level of 0.05.